A Field-Oriented Control algorithm with Multi-Sensor Data Fusion for permanent magnet synchronous motor: Design, analysis and experiments - Mattohti, Mamataziz; Dong, Yongjun; Guo, Jingfu (Measurement : journal of the International Measurement Confederation, 2025)
Precise speed control is essential for optimizing the stability, safety, and reliability of Permanent Magnet Synchronous Motor (PMSM) systems. In this paper, we propose a Field-Oriented Control (FOC) strategy enhanced with Multi-Sensor Data Fusion (MSDF) to improve the accuracy of PMSM speed control. The strategy integrates Hall sensors and an Extended Kalman Filter (EKF) to estimate the required rotor position and speed, which are then processed through MSDF to provide more accurate values for FOC. Simulation results demonstrate that this approach significantly outperforms using Hall sensors or EKF alone in terms of speed accuracy, a finding that is further validated by experimental results. Notably, the proposed method delivers a faster response in speed regulation during PMSM startup and speed changes. Additionally, even in the presence of magnetic interference affecting Hall sensors during steady-state operation, the control system maintains speed with greater stability and accuracy. This research provides a novel FOC algorithm for achieving stable and high-precision speed control of PMSMs. [Display omitted] •A new method for stable and high-precision speed control of PMSMs is proposed.•The MSDF integrates multi-source data to enhance rotor position and speed accuracy.•Simulations and experiments validate the superior performance of the proposed method.